PROXY WARS IN CYBERSPACE - Torres Soriano, Manuel Ricardo (Journal of the Spanish Institute for Strategic Studies, 2018)
This article proposes an in-depth study into the specific dynamics ofcyberspace as a stage onto which to project so-called “proxy wars”. Itsbasic thesis is that the main advantage which this strategy provides(low risk of retaliation by the actor under attack) is also its principalweakness, since indirect participation in a cyber conflict detractsfrom a State’s efficiency in reaching tactical objectives, and is of onlymoderate value for advancing towards the achievement of strategicobjectives. Throughout the paper, analysis is made of the advantagesand limitations of this strategy, and a typology of the various cyberproxies is proposed based on their relation to the State utilizing them.
Keywords: Cyberspace; conflicts; espionage; deterrence; hacktivism